SAFETY DOOR WITH COMPUTER-BASED PASSWORD - Mukti Husodo; Irwan Numara, Ir, MM (Jurnal Sistem Komputer, 2000)
The address indicates a location, for that address is unique, so there is only onelocation with one address.Address used on the PC processor to be able to communicate with each section aswell as on the PC to be able to communicate or control the application work as asafety door.